Meningkatkan Kecerdasan Emosi Siswa: Pengaplikasian Model Pengembangan Kecerdasan Emosi Berbasis Konseling Perkembangan - Helma Helma; Yasrial Chandra; Randi Saputra (Program Studi Bimbingan dan Konseling FKIP UMSU, 2020)
The purpose of this research is to find out the effort to improve students' emotional intelligence by applying the development of emotional intelligence based on development counseling models. This research uses quantitative methods. The population in this study was state high school students (SMAN) in Padang City, involving as many as 300 high school students as a sample. The instrument used was the Emotion Intelligence Scale inventory. The effectiveness test of the development of emotional intelligence based on development counseling is done through ANCOVA. The results showed that the development model of emotional intelligence based on effective development counseling.